The bond and money markets : strategy, trading, analysis - Choudhry, Moorad (Boston : Butterworth-Heinemann, 2001)
Explains and analyses all aspects of the bond and money markets and is both an introduction for newcomers and an advanced text for experienced market practitioners and graduate students.
Includes bibliographical references and index.
oif 19/08/15
Loans
Keywords: Bonds; Money market; Money market - Trading; Bond and money market